Classifying Consumers Based Upon Their Proenvironmental Behaviour: An Empirical Investigation - G. Modi, Ashwin; D. Patel, Jayesh (Asian Academy of Management (AAM), 2013)
Despite a wide applicability of demographic and psychographic variables for segmentation criteria, past research indicates that these variables are not as effective as behavioural variables. The present empirical study’s focus is determining different typologies of Indian consumers, which exist in terms of Pro-Environmental Behaviour (PEB), and investigating whether PEB varies across these typologies. For this study, a total of 152 Indian consumers were contacted through convenience sampling. Using factor and cluster analysis, the typologies were classified as “active green activists” or “passive green activists”. Using discriminant analysis, formed groups were validated and profiled by chi-square. Using environmental variables as the basis of segmentation, this study offers practical guidelines to green marketers who are targeting the Indian markets.